Build a robot for data simulation and signal processing in the financial market - Liew, Liyuan. (2009)
This report introduces the foreign exchange market. Due to global interest of the foreign exchange market which has now amount to about $4 trillion in trading volume per day, this report focuses on the mathematical tools available to traders to trade in this market. These tools are known as technical indicators and they contain mathematical formulas to derive the sentiment of the market, whether the market is generally in an uptrend or downtrend. This report also shows how the author has developed his strategies using the scientific method which basically comprises of characterization of data, making hypothesis, predictions and carrying out experiments based on them. The report briefly discusses on the process of data mining and backtesting as means to developing strategies. This report also discusses on the advantages and disadvantages of using the Expert Advisor which is basically a robot that can help the user to execute trades in the forex market automatically. Strategies can be tested by making use of the Expert advisor and results are displayed very quickly compared to the method of using manual backtesting. The completion of this FYP has led to the conclusion that mathematical tools and robots like the expert advisor can help traders to a certain extent but psychology of the traders themselves are also vital in gaining and protecting profits in the market where extreme emotions are in play all the time.